Analisis Keragaman Genetik Kelompok Pleurotus dengan Teknik Polymerase Chain Reaction- Restriction Fragment Lenght Polymorphisms (PCR-RFLP) - Elis Nina Herliyana; Reny Meisetyani; Iskandar Z Siregar (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Analysis of Genetic Variability of Pleurotus group with Polymerase Chain Reaction-Restriction Fragment Lenght Polymorphisms (PCR-RFLP) TechniqueThe research was done in Forest Pathology Laboratory and Sylviculture Laboratory, Forest Faculty, Bogor Agriculture University. The observed is too know the genetic variability of Pleurotus group and compare it with the morphological variability also applications of PCR-RFLP in Pleurotus group.PCR-RFLP using the primers ITS1 and ITS4 can be applied to the Pleurotus group. The use of Alui restriction enzymes can give results ribbon cutting DNA from PCR-RFLP results. The result of genetic variability by PCR-RFLP showed differenced compare to genus and morphological variability.